Value-based total performance excellence measurement: an overview of agenda and transformation - Mokhtar Abdullah,; Mohd Rashid Ab Hamid,; Zainol Mustafa,; Nur Riza Mohd Suradi,; Fazli Idris,; Choong-Yeun Liong,; Wan Rosmanira Ismail,; Faridatulazna A. Shahabuddin, (Penerbit Universiti Kebangsaan Malaysia, 2011)
The process of performance measurement has undergone a revolution from measuring things outward to measuring things that are not apparent. In other words, the overall performance of non-financial nature has also been given a serious attention. Integration of the use of both elements of performance indicators involving both financial and non-financial should be used to assess the performance of the organisation. This is because not only the satisfaction of the external customer has to be fulfilled for survival of the organisation but also the internal customer satisfaction is equally important in ensuring the success of the organisation.Therefore, this article expounds the suggested implementation of the Performance Measurement System which showcases an overview of intangible aspects of measurement i.e.organisational core values through Value-Based Total Performance Excellence Model. This model would reveal overall standings and achievements of the public agencies and indicate opportunities for further improvements based on the value-based indicators. Implications of the study is significant to the public organisation for enhancing and empowering the valuebased assessment approach which emphasised more on intangibles aspects of measurement rather than on tangibles aspects only. This is vital in ensuring that human resources in the organisation have truly embraced the organisational core values and endeavouring for achieving a total organisational excellence as emphasised in the 1Malaysia concept – ‘People first, Performance now’